The first Triassic lungfish from South America (Santa Maria Formation, Paraná Basin) and its bearing on geological correlations within Pangaea - Richter, M.; Toledo, C. E V [UNESP] (Geological Society of London, 2008)
The Triassic fish faunas of the Southern Hemisphere are only known from a few sedimentary basins and the most productive sites are those from the Karoo Supergroup, in South Africa and the Sydney Basin of Australia. A single lungfish tooth plate ascribed to Ptychoceratodus cf. philippsi was recovered from Late Triassic (Carnian) red beds of southern Brazil and is described herein. This find extends to South America the palaeogeographic distribution of the genus, which occurs in the Early Triassic of Australia and South Africa and the Middle/Late Triassic of Europe and Late Triassic of Madagascar and India. The presence of this dipnoan solely in the uppermost part of the Santa Maria Formation suggests that the migration of Ptychoceratodus towards the Paraná Basin began not before the late Induan/early Olenekian (late Early Triassic). At that time, more humid (monsoonal) conditions prevailed in what is now southern Brazil, compared to semi-arid/desert conditions that dominated the Late Permian and possibly the earliest Early Triassic (the latter presumably not represented in the Paraná Basin). © The Geological Society of London 2008.
Keywords: fish; geographical distribution; new genus; new species; paleogeography; population migration; Southern Hemisphere; species occurrence; tooth; Triassic; Africa; Asia; Australasia; Australia; Eurasia; India; Indian Ocean; Indian Ocean islands; Karoo; Madagascar; New South Wales; Parana Basin; South Africa; South America; South Asia; Southern Africa; Sub-Saharan Africa; Sydney Basin